ANALISIS MOTIVASI BELAJAR SISWA DAN KEMAMPUAN BERPIKIR KRITIS SISWA SMA NEGERI 1 TEBING TINGGI PADA PEMBELAJARAN FISIKA SELAMA MASA PANDEMI COVID-19 - Sinta Sonia; Rosane Medriati (Universitas Sriwijaya, 2022)
The purpose of this study was to determine students' learning motivation in learning physics during the covid-19 pandemic and to identify students' critical thinking skills in physics lessons during the covid-19 pandemic. This type of research is descriptive research. Descriptive research is a research method that describes the characteristics of the population or phenomenon being studied. The sampling technique in this study was purposive sampling. The research instrument used was a questionnaire with a Likert scale of five addressed to students of class XI MIPA 1 & XI MIPA 2 SMA Negeri 1 Tebing Tinggi. The results of this study indicate that the students' motivation to learn physics in grades XI MIPA 1 & XI MIPA 2 SMA Negeri 1 Tebing Tinggi on the intrinsic motivation dimension comes from indicators of high learning activity tends to be quite good criteria with a percentage of 61% and on the extrinsic motivation dimension comes from indicators of presence information from teachers tends to be very good with a percentage of 59%. The results of the student's critical thinking ability test obtained by testing student learning outcomes from several test questions in this study showed that 76.3% of students had critical thinking skills in the very high category, 20.3% of students had critical thinking skills in high category, and 3.4% of students have critical thinking skills in the medium category. There are no students who have critical thinking skills in the low and very low categories. Keywords: learning motivation, indicators, critical thinking skills, learning outcomes, covid-19